The War for Muslim Minds : Islam and the West - Kepel, Gilles (Cambridge, London Belknap Press of Harvard University Press, 2004)
"Kepel examines the impact of global terrorism and the ensuing military operations to stem its tide. He questions the United States' ability to address the Middle East challenge with Cold War rhetoric, while revealing the fault lines in terrorist ideology and tactics. Finally, he proposes a way out of the Middle East quagmire that triangulates the interests of Islamists, the West, and the Arab and Muslim ruling elites. That path leads through Muslim immigrant communities in the West--the ultimate battlefield where the struggle for the democratization of Islamic societies will be won or lost"--Jacket.
Include Sources and Index
Keywords: East and West -- War on Terrorism (2001-2009) -- Islam -- 21st Century